47. MANIFESTATIONS OF DEPRESSION, ANXIETY, AND STRESS OF STUDENTS AT CA MAU MEDICAL COLLEGE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of depression, anxiety, and stress symptoms among students and some related factors.Method: A cross-sectional descriptive study was conducted on 796 students from Octorber 2024 to December 2024.Results: The rates of students with symptoms of depression were 31.16%, anxiety 51.26%, and stress 34.42%. There was a statistically significant association between gender, family circumstances, tuition costs, part-time work and depression, anxiety and stress, p < 0.05, while stress levels gradually decreased in later year students compared to freshmen.Conclusion: Depression, anxiety, and stress affect more than 1/3 of students, with anxiety being a health issue of concern. Vulnerable students such as females, those lacking family support, and those with emotionally deprived family environments also need more attention.
Keywords: Depression; anxiety; stress; DASS-21.